Passthrough of Firm Performance to Income and Employment Stability - Jonas Maibom; Rune Majlund Vejlin (Institute of Labor Economics (IZA), 2021)
To what extent do firms pass through idiosyncratic shocks to their workers? In this paper, we investigate this question focusing on passthrough to income for workers that stay in the firm and passthrough to employment stability. We take an empirical approach and use matched employer-employee data from Denmark, three different measures of firm performance (sales, value added, and value added per worker), and two measures of income (earnings and hourly wages). We distinguish between unemployment and job-to-job transitions. We find that passthrough to income is much higher for permanent (5-9 percent) than transitory (1 percent) shocks. Income passthrough is higher for blue collar workers and workers in small firms. On the employment margin, we find that worse firm performance increases both unemployment and job-to-job transitions. The unemployment risk is especially pronounced for blue collar, low-educated, low tenure workers, while the effect on job-to-job transitions is larger for managers and high-educated workers. We also find clear evidence of non-linearities with negative shocks driving both unemployment and job-to-job transitions.
Keywords: C33; D22; J31; J33; 330; firm shocks; passthrough; income; employment stability